Cerebral blood flow increases during insulin-induced hypoglycaemia in type 1 (insulin-dependent) diabetic patients and control subjects. - Neil, H; Gale, E; Hamilton, S; Lopez-Espinoza, I; Kaura, R; McCarthy, S (Springer-Verlag, 1987)
The effect of insulin-induced hypoglycaemia on cerebral blood flow was examined using the intravenous xenon-clearance technique in 9 patients with Type 1 (insulin-dependent) diabetes (aged 20 to 43 years) and 9 age-matched control subjects before, during and after hypoglycaemia. Cerebral blood flow rose in both groups. The mean basal cerebral flood flow values were not significantly different and during hypoglycaemia mean cerebral blood flow increased by 17% (p = 0.008) in the diabetic patients and by 21% (p = 0.0003) in the control subjects. The results suggest that in young diabetic patients without autonomic neuropathy or microangiopathy cerebral vessels dilate normally in response to hypoglycaemia. The physiological importance of an increase in cerebral blood flow during hypoglycaemia is uncertain; but glucose availability is increased.